2001
DOI: 10.1002/nbm.716
|View full text |Cite
|
Sign up to set email alerts
|

Issues in flow and oxygenation dependent contrast (FLOOD) imaging of tumours

Abstract: The sensitivity of blood oxygenation level dependent (BOLD) contrast techniques to changes to tumour deoxyhaemoglobin concentration is of relevance to many strategies in cancer treatments. In the context of tumour studies, which frequently involve the use of agents to modify blood flow, there are underlying physiological changes different to those of BOLD in the brain. Hence we use the term, flow and oxygenation dependent (FLOOD) contrast, to emphasize this difference and the importance of flow effects. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
175
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(181 citation statements)
references
References 34 publications
(61 reference statements)
4
175
0
2
Order By: Relevance
“…Because the bSSFP signal approximately scales with the R 1 /R 2 ratio (46), this can also be explained by a reduced dHb concentration (R 2 decrease) as well as by an increase in PO 2 and an elevated inflow of unsaturated spins: both manifest in an enhancement of the true and apparent R 1 , respectively (16,30). With long TE and TR, the bSSFP signal further exhibits a considerable T* 2 contrast and Miller et al have shown that gradientecho and passband bSSFP signals behave similarly at long TR (34,35), which could be another explanation of the bSSFP signal increase.…”
Section: Discussionmentioning
confidence: 99%
“…Because the bSSFP signal approximately scales with the R 1 /R 2 ratio (46), this can also be explained by a reduced dHb concentration (R 2 decrease) as well as by an increase in PO 2 and an elevated inflow of unsaturated spins: both manifest in an enhancement of the true and apparent R 1 , respectively (16,30). With long TE and TR, the bSSFP signal further exhibits a considerable T* 2 contrast and Miller et al have shown that gradientecho and passband bSSFP signals behave similarly at long TR (34,35), which could be another explanation of the bSSFP signal increase.…”
Section: Discussionmentioning
confidence: 99%
“…The tip angle chosen in the GRE pulse sequences in the imaging experiments was sufficient to elicit BOLD contrast caused by changes in both tissue oxygen concentration and blood flow (15,16). The present study shows that the core temperature of a female C3H mouse steadily decreases from 37°C to 30°C within Ïł20 min.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its very large application in neuroscience, the use of BOLD contrast in tumor brings with it new challenges of understanding and interpretation. 100 The underlying physiological changes are different from those of BOLD in the brain. In the brain, blood vessel size, density and distribution are well characterized, in contrast to tumors.…”
Section: Techniques For the Assessment Of Tumor Oxygenationmentioning
confidence: 99%
“…113 Changes in R Ã 2 in response to a vasoactive challenge are not always predictable. 100 An R Ã 2 decrease is expected in response to agents aimed at improving tumor oxygenation and blood flow, and conversely an increase in R Ã 2 is expected with agents designed to increase tumor hypoxia. However, changes in blood volume can counteract the effect of blood oxygenation changes.…”
Section: Techniques For the Assessment Of Tumor Oxygenationmentioning
confidence: 99%